Does the intensity of deliberate late-gestation exercise impact body composition and milk components in dairy heifers? - Randol, Jamy Fay (My University, 2025)
The initiation of lactation in dairy cattle often results in adipose and skeletal muscle mobilization. Our objective was to determine if exercise affects body composition, total milk production, or milk components in nulliparous pregnant heifers. We hypothesized that exercise may improve physiological responses to increased nutrient demands during lactation by mildly and regularly altering homeostasis and improving adipose or skeletal muscle storage and subsequent catabolism. Nulliparous, pregnant Holstein heifers (n=34) were enrolled in 2 cohorts based on the expected calving date (90.27 ± 6.35 d prepartum) for two concomitant 8-week exercise trials. Heifers in each cohort were stratified into one of three treatment groups based on pre-trial subcutaneous (SQ) fat over the proximal gluteobiceps (thurl)). Treatments were administered Mon, Wed and Fri with an 8-panel motorized free-walker, and included sedentary (SED; penned adjacent to free-walker), low intensity (LI; pace estimated to achieve 70% lactate threshold), and high intensity (HI; pace estimated to achieve 130% of lactate threshold in short intervals). Both LI and HI groups walked the same distance for each exercise bout, ranging from 1km to 3.04km. Treatment ceased at 33.96 ± 6.92 d prepartum. Weekly during treatment, heifers were weighed, and ultrasound was used to quantify SQ adipose thickness, and semitendinosus depth, width, and area. Postpartum carryover effects on milk yield (daily) and components (1 d/wk) were assessed for 10 wk. Cohort data were combined; data were analyzed using a one-way repeated measures SPSS (Version 29.0.2.0) with significance determined at P < 0.05. Exercise, regardless of intensity, caused significantly reduced SQ adipose thickness throughout the exercise period compared to SED. Exercise also increased semitendinosus dimensions (P = .03), with HI exercise increasing (Tukey separated means; P < 0.05) muscle area (.042 vs. .058 and .987), depth (.053 vs. .334 and .548), and width (.003 vs. .104 and. .242cm) compared with SED and LI. During the first 10 weeks of lactation, heifers that underwent high intensity exercise exhibited less rapid SQ fat loss. Heifers that underwent high intensity exercise also retained greater semitendinosus area (.004; .02 vs. .137 and .135 cm) during the first 10 wks of lactation. Both HI and LI retained greater semitendinosus depth (<.001 vs. .009 and .055 mm) and semitendinosus width (P = XX; <.001 vs. <.001 and .094 mm) compared to SED. Exercise, regardless of intensity, impacted body weight and BCS through the first 10 weeks of lactation, with heifers that underwent high intensity exercise losing both weight and condition less rapidly, along with recovering body weight and body condition more quickly. Exercise did not affect milk yield, composition, or component yield. In summary, primarily high-intensity late-gestation exercise increased overall muscle size prepartum and prevented loss of fat thickness and muscle size postpartum without affecting total production and milk components. We conclude that strategic exercise regimens could improve adaptation to the catabolic demands of lactation in nulliparous heifers.
Keywords: Dairy heifers; Exercise; Body composition; Milk composition